2014
DOI: 10.1016/j.ijid.2014.03.1392
|View full text |Cite
|
Sign up to set email alerts
|

Severe dengue outbreak in Yunnan, China, 2013

Abstract: In recent decades, the impact of dengue has increased both geographically and in intensity, and this disease is now a threat to approximately half of the world's population. An unexpected large outbreak of dengue fever was reported in Xishuangbanna Dai Autonomous Prefecture, Yunnan Province, China, in 2013. This was the first autochthonous outbreak with a significant proportion of severe dengue cases in mainland China in a decade. According to the 2009 World Health Organization guidelines, half of the 136 labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 9 publications
4
59
1
Order By: Relevance
“…The distribution of Ae. aegypti in Xishuangbanna was firstly found in 2013 during dengue epidemic there [1]. From the surveillance results from June to December, 2014, there were 647 positive containers for Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of Ae. aegypti in Xishuangbanna was firstly found in 2013 during dengue epidemic there [1]. From the surveillance results from June to December, 2014, there were 647 positive containers for Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti in Dehong DaiJingpo Autonomous Prefecture, Yunnan province, China. According to previous studies [1], it was reported that Ae. aegypti was detected for the first time in Xishuangbanna, and we found the two important dengue vectors, Ae.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Three individual studies have reported the dengue outbreaks occurred in Yunnan and Henan Provinces in 2013 [1921]. However, no study tried to explore the transmission dynamics between locations.…”
Section: Introductionmentioning
confidence: 99%
“…Aedes albopictus, the primary vector for DENV in Guangdong, can transmit DENV transovarially, thus overwintering mosquitoes may serve as potential source of dengue to initiate a new infection cycle. Importantly, Aedes aegypti, the more effective DENV vector than Aedes albopictus, has been introduced and colonized southern regions of China, including Yunnan and Guangdong provinces [2]. It is likely that DENV will establish its infection in Chinese Aedes aegypti, which can further deteriorate the current situation.…”
mentioning
confidence: 99%